Analysis of Knowledge Factors and Attitudes Affecting Behavior Health Handling Behavior In Preschool Children - Heri Saputro; Ndamung Matalu (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Behavioral engagement of the mother to the child needs to be understood in taking a treatment or therapeutic action that can reduce body temperature in children and behavioral handling in influencing factors knowledge and attitude that can help in the handling of fever. The purpose of this study to determine the factors of knowledge and attitude of mothers that affect the behavior of home fever handling in preschool children in the work area UPTD Community Health Clinik Cement District Kediri.The design of this research is observation / survey with cross-sectional approach. Total sampling technique. Samples in this study all the mothers as much as 45 people. Independent variable to be studied is Knowledge, attitude of dependent variable is handling behavior. The statistical test used is logistic regression.The result of the research showed that mother's knowledge on fever handling behavior in the category was 17 respondents (37,8%), positive category was 21 respondents (46,7%). From the analysis of data knowledge shows the value of P value = 0.021 <α 0.05 so that H1 is accepted which means there is influence of mother's knowledge on fever handling behavior and attitude show value P value = 0,017 <α 0,05 so that H1 accepted which mean there is influence of mother attitude on the behavior of fever handling. The statistic overal result (0,012) <α (0,005) means there is influence of knowledge, attitude, simultaneously to behavior of home fever handling at preschool children at UPTD Community Health Clinik Cement District Kediri.Handling fever is influenced by knowledge and attitude of mother because in determining child recovery process determined from mother understanding about prevention of bacteria, virus and microorganism and mother response in effort to prevent fever by giving warm compress therapy or pemeberian of febrifuge to reduce body temperature